How does economic crisis change the landscape of real convergence for Central and Eastern Europe? - Ileana Alexe (Romanian Journal of Fiscal Policy (RJFP), 2012)
The paper aims at analyzing the impact of the recent economic crisis on the real convergence with the Euro area for ten countries from Central and Eastern Europe that joined the European Union in 2004 and 2007. We use 2000, 2008 and 2010 as benchmark years for our study and GDP per capita at PPP, as the most relevant indicator in terms of real convergence. The study is based on Euclidian distance analysis. The results reveal that most of the countries recorded higher distances from the Euro area average, while Poland and Slovakia improved their convergence.
Keywords: F15; F43; C82; 330; real convergence; Euclidian distances; Central and Eastern Europe; Euro area